Implementation of direct seeding for malting barley production in the state of Guanajuato - Báez-Pérez, Aurelio; Arreola Tostado, Jesús Manuel; Triomphe, Bernard; Bautista Cruz, Angélica; Licea Morales, Pablo de Jesús (Revista Mexicana de Ciencias Agrícolas, 2018)
At present, the profitability of grain production in the Bajío has been impacted by the excessive increase in the price of chemical fertilizers and other agricultural inputs; due to soil degradation and the depletion of groundwater. Because of this it is necessary to implement farming practices that lead to reverse this problem. For this purpose, an experiment was established in the Experimental field of the Bajío in Celaya, Guanajuato, to evaluate the production of barley (Hordeum vulgare L.) under different agronomic practices based on No-till farming or direct planting (DP). Previous to the experiment, a crop of maize (Zea mays L.) was established during spring-summer 2006, to produce the crop residue needed for the implementation of the DP. During the autumn-winter cycle was evaluated the production of barley of the variety Esperanza under two cropping systems: conventional tillage (CT) and DP; three doses of nitrogen fertilization (urea): 90-60-00, 180-60-00 and 270-60-00, and three irrigation systems: sprinkler, surface with intermittent flow and surface with continuous flow. It was used a factorial experimental design 2 x 3 x 3 with 18 treatments and arranged in randomized blocks. There were established from four to eight replicates per treatment. The soil moisture was monitored. The production of barley grain was about 20% higher in DP compared to CT. There were significant effects (p< 0.05) by the factors: type of planting and fertilization doses, not by the type of irrigation. A strong interaction prevailed (p< 0.05) between the type of planting and fertilization dosages. In DP the moisture in the soil (0-30 cm depth) before each irrigation was applied, on average, 6% higher, relative to CT (p< 0.05). According to the characteristic curve of soil moisture retention, the available moisture was between 27 and 49% humidity, so that 6% reserve, equivalent to approximately one quarter of the available moisture.
Keywords: cereals; conservation tillage; onservation practices